الإفصاح المحاسبي في القوائم المالية للمصارف وفقاً للمعيار المحاسبي الدولي رقم (30) "حالة تطبيقية في المصرف التجاري السوري" - زيود لطيف; الرضا عقبة; لايقة رولا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يساهم تطبيق معايير المحاسبة الدولية في تحسين نوعية المعلومات المحاسبية المقدمة لمختلف فئات المستخدمين، وذلك من خلال تقديم معلومات ملائمة وقابلة للفهم وذات موثوقية عالية، كما أنها تساهم في جعل المعلومات المحاسبية قابلة للمقارنة مع المعلومات للمنظمات الأخرى وبين القوائم المالية للمنظمة نفسها لفترات زمنية متعددة. وللمصارف والمؤسسات المالية طبيعة خاصة من حيث العمليات التي تجريها، وبالتالي العوائد والمخاطر التي تتعرض لها مما دفع لجنة معايير المحاسبة الدولية إلى وضع معيار مستقل للإفصاح في القوائم المالية للمصارف والمؤسسات المالية المشابهة رقم (30)، وبالتالي فإن تطبيق معايير المحاسبة الدولية في المصارف يعد مدخلاً ضرورياً للوصول إلى معلومات تساعد متخذي القرار على تقويم المركز المالي والأعمال والإنجازات التي تقوم بها المصارف وفهم المميزات الخاصة لطبيعة أعمال المصارف. The application of international financial standards helps in improving the kinds of the supplied accounting information of various types of users through presenting suitable and comprehensible highly reliable information. It also helps to make accountancy information comparable with information of other organizations and financial statements of the organization itself for different periods of time. Banks and other financial establishments have special nature from the point of view of operations carried by them, along with the income and risks faced by them, which forced the international accountancy standards committee to put forth an independent standard of disclosure of the financial statement of banks and of similar financial establishment no. (30). Consequently, the application of international accountancy standards by banks is considered a necessary step to reach the information that helps decision makers to evaluate the financial position, the work, and achievement carried out by banks, and to understand special characteristics of the nature of the work of banks.